Financial Incentive Does Not Affect P300 in the Complex Trial Protocol (CTP) Version of the Concealed Information Test (CIT) in Malingering Detection. II. Uninstructed Subjects - Rosenfeld, J. Peter; Davydova, Elena; Labkovsky, Elena; Ward, Anne (Frontiers in Psychiatry, 2019)
Previous research indicated that the skin conductance response (SCR) of the Autonomic Nervous System (ANS) in the CIT is typically increased in subjects who are financially and otherwise incentivized to defeat the CIT; (the paradoxical “motivational impairment” effect). This is not the case for RT-based CITs, P300 CITs based on the 3-stimulus protocol, nor on the P300-based complex trial protocol for detection of cognitive malingering (although these are not the same as forensic CITs). The present report follows up the Rosenfeld et al. (2017) study of motivated malingerers instructed how to beat the test, with uninstructed motivated (paid and unpaid) and unmotivated (“simple malingering”) subjects, using episodic and semantic memory probes. The Test of Memory Malingering (TOMM) was used to validate behavioral differences among groups. The “CIT effect” (probe-minus-irrelevant P300 differences) did not differ among incentive groups, although as previously, semantic memory-evoked P300s were larger than episodic memory evoked P300s. An effect of specific test-beating instructions was found to enhance the CIT effect for semantic information.